2010
DOI: 10.1111/j.1447-0594.2010.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of aldehyde dehydrogenase 2 gene polymorphism with pancreatic cancer but not colon cancer

Abstract: Aims:Most of the acetaldehyde, a recognized animal carcinogen, generated during alcohol metabolism is eliminated by liver mitochondrial aldehyde dehydrogenase 2 (ALDH2). More than 40% of Japanese people have the inactive form of ALDH2, and inactive ALDH2 is a risk factor for multiple cancer of the esophagus, as well as head and neck cancer. Possible associations between pancreatic cancer and ALDH2 gene polymorphism, as well as between colon cancer and ALDH2 gene polymorphism, in conjunction with smoking and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Finally, eleven studies met the inclusion criteria (comprising 2909 cases and 4903 controls). Genotype distributions in the controls of Chiang's study[15] and Miyasaka's syudy[16] were not in agreement with the HWE. The detailed characteristics of the studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Finally, eleven studies met the inclusion criteria (comprising 2909 cases and 4903 controls). Genotype distributions in the controls of Chiang's study[15] and Miyasaka's syudy[16] were not in agreement with the HWE. The detailed characteristics of the studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 75%
“…Therefore, further studies are warranted in other high risk areas. Fourthly, although the genotype distributions in the pooled controls from the included studies were in agree with HWE, genotype distributions in the controls from Chiang's study[15] and Miyasaka's study[16] were not in agreement with HWE, therefore, the results may be biased. Lastly, publication bias may have occurred, although the funnel plot did not indicate this; negative findings were likely to be unreported.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…No association between liver cancer and ALDH2*2 alone was initially reported (68); however, a risk may be associated with hepatitis C infection (75). Conflicting results have also been found for colon cancer (76, 77). …”
Section: Impact On Human Healthmentioning
confidence: 96%
“…Matsuo et al reported that high level of alcohol consumption was associated with an increased rectal cancer risk but not colon cancer risk among individuals with ALDH2*1/*2 [46]. Miyasaka et al found no association between ALDH2*2 and colon cancer and did not assess the interaction between ALDH2*2 and alcohol drinking on colon cancer risk [47]. Overall, the role of ALDH2*2 in the development of colorectal cancer is inconclusive and all of the studies conducted to date have a small sample size that resulted in insufficient statistical power and lack of precision.…”
Section: Aldh2 Polymorphism and Risk Of Alcohol-related Cancersmentioning
confidence: 99%